The mathematical creative thinking ability of students viewed from learning motivation by using Treffinger learning model - Amanoe, Zihni; Isnarto, Isnarto (Unnes Journal of Mathematics Education, 2021)
The purpose of this study were to (1) know the achievement of the guidance to learn the skills of mathematical creative thinking students in Treffinger learning, (2) know the increase of students ' mathematical creative thinking skills in Treffinger learning, and (3) describe students' mathematical creative thinking skills for each category of learning motivation in Treffinger learning. This research method is a mixed methods design with sequential explanatory. The population in the study were all students of class VII Junior High School 3 Semarang Year 2019/2020, and sampling was conducted by random sampling selected to be sampled is a class VII-H. The subject of research conducted by purposive sampling technique. Subjects consisted of 6 students. Subjects were interviewed by the results of tests of creative mathematical thinking skills and student motivation. The results showed that (1) students' mathematical creative thinking abilities in Treffinger learning achieve mastery learning. (2) There is an increase in students' mathematical creative thinking skills in Treffinger learning. Increased mathematical creative thinking skills are medium. (3) Subject to high learning motivation can meet the indicators flexibility, fluency, and novelty. Subject to being able to meet the learning motivation fluency and novelty or just fluency. Subjects with low learning motivation are only able to meet one indicator fluency.